ASSOCIATION BETWEEN ARRANGEMENT OF PUBLIC SPACE AND PEOPLE BEHAVIOR (CASE STUDY: MANGGAR RIVERBANK SETTLEMENT) - Jordan, Nadia Almira; Ulimaz, Mega (Border: Jurnal Arsitektur, 2019)
The meaning of space is one aspect of a successful public space which is seen by social interaction between users of the space. Existence of social interaction in residential areas as living spaces with a relatively high density and proximity can support the vitality of urban areas. The purpose of this study is to obtain a relationship between the formation of public space and the activities of the inhabitant or community, especially in riverbank settlements. Qualitative research methods are used to get a real picture of the situation or setting in the public spaces based on interpretations of direct observation. Researchers' observations are based on a literature review of open space and people's behavior in the public spaces. As part of the process of understanding the facts, street survey techniques were carried out in three open spaces in the Manggar settlement area to determine the pattern of space user activity in terms of penetration, action patterns, behavior mechanisms, and welfare. The results showed that public open space was formed through routine activities of the community naturally, through the process of selecting places close to work access.